Metáforas del cuerpo: el lenguaje artístico como recurso de la memoria (2018)
This paper analyzes the work of the Honduran organization Mujeres en las Artes (MUA) - Women in the Arts - over the past 20 years. Starting from life stories and artistic creations - such as representation, interpretation and explanation of the everyday world - the body is considered as territory, as a metaphor that mediates personal and collective processes. Therefore, the artistic language endures memories and provides meaning to life. As a consequence, - violence, trauma, marks, oblivion and silence confront the paradigmatic discourses that support culture and science; declaiming for knowledge and learning of what the body is able to explore, as warned by Merleau Ponty.